On some questions of the composition analysis of municipal property in the Russian Federation - Isaeva, Kristina Vadimovna; Kuznetsov, Aleksandr Aleksandrovich; Zalesny, Yatsek; Goncharov, Vitalii Viktorovich (Юридические исследования, 2021)
This article is dedicated to the composition analysis of municipal property in the Russian Federation. Being the grassroots of the system of administrative-territorial division of the country, the municipalities in the Russian Federation have a considerable number of the objects of municipal property. Therefore, it requires effective administration and appropriation in full accordance with the rights, freedoms and legitimate interests of the citizens residing on the territory of these municipalities. The article provides the original definition of municipal property, which implies property complex of the municipality, including items of property owned by municipalities. The authors explore the composition of municipal property in the Russian Federation analyzing the legal consolidation of the key types of its items, as well as the practice of exercising the right to municipal property by municipalities with regards to certain items of municipal property. The article formulates and substantiates the recommendations for improving the legislation of the Russian Federation that regulates the questions of municipal property. The authors believe that the implementation of such proposals would enable effective administration and appropriation of municipal property in the interests of citizens of the Russian Federation.